Predictors of re-exacerbation after an index exacerbation of chronic obstructive pulmonary disease in the REDUCE randomised clinical trial (Swiss Medical Weekly, 2017)
BACKGROUND Acute exacerbations of chronic obstructive pulmonary disease (AECOPD) compromise physical activity and quality of life and contribute significantly to health care costs. Systemic glucocorticoids benefit clinical outcome in AECOPD, and the REDUCE trial demonstrated noninferiority of a 5-day treatment course with prednisone compared with 14 days therapy regarding clinical outcome over 6 months of follow-up. Unexpectedly, we found an inverse correlation between circulating cortisol levels and exacerbation risk during a 6-month follow-up period. OBJECTIVE To evaluate whether additional predictors of COPD re-exacerbation can be identified after the index exacerbation in the REDUCE cohort. METHODS Of 314 patients with AECOPD randomised to 5 or 14 days of prednisone treatment, 311 were included in the analysis. Parameters tested as predictors of re-exacerbation were sex, age, smoking status, forced expiratory volume in one second (FEV1), dyspnoea as assessed with the Medical Research Council (MRC) dyspnoea scale, home oxygen therapy, pretreatment with systemic glucocorticoids, pretreatment with antibiotics, duration of hospitalisation, blood pressure, oxygen saturation, admission to the Intensive Care Unit (ICU) and relevant infections in follow-up. The risks for re-exacerbation were estimated by means of logistic regression and Cox proportional hazard models and expressed as odds ratios and hazard ratios, respectively. RESULTS After multivariate adjustment, significant predictors at hospital discharge for COPD re-exacerbation during follow-up were: duration of hospital stay >8 days (hazard ratio [HR] 1.54, 95% confidence interval [CI] 1.03–2.28); FEV1